Polarographic Studies of Bi(III) Complexes with a-Alanine and L-Valine at Different Temperatures - Kajala, Anita; Singh, Jyoti; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The stability constants of Bi(III) with a-alanine and L-valine have been determined polarographically at 304 and 314 K in aqueous medium. DeFord and Hume's method was used to calculate the stepwise formation constants. The mathematical Mihailov method was also used. The reduction of the system in each case is quasireversible and diffusion controlled involving three electrons. The constant ionic strength (μ = 1 M) has been maintained using KNO3 as a supporting electrolyte. Gellings method was used to calculate Er 1/2 values for Bi(III) complexes. The complexes with metal to ligand ratio as 1:1, 1:2, 1:3 have been formed. The thermodynamic fuctions (DGº, DHº and DSº) have been calculated to understand the temperature effect on the stability of the complexes.